Giant keratoacanthoma in a patient with acquired immunodeficiency syndrome treated with Mohs micrographic surgery - Paula Hitomi Sakiyama; Thiago Augusto Ferrari; Raíssa Rigo Garbin; Alexandre Luiz Weber (Sociedade Brasileira de Dermatologia (SBD), 2020)
Keratoacanthoma (KA), although frequent in clinical practice, is a tumor that raises questions. The most intriguing aspect is associated with its position on the border between malignancy and benignity. The approach to the tumor, as well as its classification, is controversial. When defining the conduct, it is essential to consider the potential for transformation into squamous cell carcinoma. Thus, surgical excision is the therapy of choice, whenever possible. Some cases require additional attention, such as associated immunosuppression. In this article, we report a case of giant KA in a patient with acquired immunodeficiency syndrome treated with Mohs micrographic surgery.